Robust and Multifunctional Kirigami Electronics with a Tough and Permeable Aramid Nanofiber Framework (Adv. Mater. 50/2022). Issue 50 (16th December 2022) - Liu, Hongzhen; Li, Hegeng; Wang, Zuochen; Wei, Xi; Zhu, Hengjia; Sun, Mingze; Lin, Yuan; Xu, Lizhi
Abstract : Wearable Electronics Kirigami designs are advantageous for the construction of wearable electronics but suitable materials that enable robust and multifunctional systems remain limited. In article number 2207350, Lizhi Xu and co‐workers report a versatile materials platform based on a composite nanofiber framework (CNFF) for the engineering of wearable kirigami electronics. The resultant devices exhibit outstanding mechanical robustness to withstand extensive 3D deformation. Various microelectronic sensors and electroactive polymers are integrated onto the CNFF‐based materials platform to achieve measurements of physiological parameters.